Antiphospholipid Antibodies Overlapping in Isolated Neurological Syndrome and Multiple Sclerosis: Neurobiological Insights and Diagnostic Challenges - D’Angelo, Chiara; Franch, Oriol; Fernández-Paredes, Lidia; Oreja-Guevara, Celia; Núñez-Beltrán, María; Comins-Boo, Alejandra; Reale, Marcella; Sánchez-Ramón, Silvia (Frontiers in Cellular Neuroscience, 2019)
Antiphospholipid syndrome (APS) is characterized by arterial and venous thrombosis, pregnancy morbidity and fetal loss caused by pathogenic autoantibodies against phospholipids and PL-cofactors. Isolated neurological APS may represent a significant diagnostic challenge, as epidemiological, clinical and neuroimaging features may overlap with those of multiple sclerosis (MS). In an open view, MS could be considered as an organ-specific anti-lipid (phospholipid and glycosphingolipid associated proteins) disease, in which autoreactive B cells and CD8+ T cells play a dominant role in its pathophysiology. In MS, diverse autoantibodies against the lipid-protein cofactors of the myelin sheath have been described, whose pathophysiologic role remains unknown. Several studies have determined a wide range of organ-specific antiphospholipid (aPL) autoantibodies in the so-called MS-like syndrome, whose presence ranging between 2% and 88%, particularly aCL and aβ2GPI, with predominant IgM isotype and suggesting worse prognosis. We have revised the current knowledge about the pathophysiological events responsible for these conditions, and the clinical relevance to be aware of isolated neurological APS. Prompt and accurate diagnosis and antiaggregant and anticoagulant treatment of APS could be vital to prevent or reduce APS-related morbidity and mortality.